IMPROVED DIAGNOSTIC AND SURGICAL TREATMENT OF PATIENTS WITH RECTOCELE - A. G. Hitar’jan; S. V. Prokudin; K. A. Dul’erov (Медицинский вестник Юга России, 2016)
Purpose: to optimize surgical tactics and improve the results of treatment of rectocele.Materials and methods: clinical group included 87 women suffering rectocele 2-3 degrees. Depending on the surgical treatment, the patients were divided into two groups. In Group 1 (n = 38) in the surgical treatment of transvaginal access comply with levatoroplastic and colporrhaphia. In Group 2 (n = 49) plastic rectocele was carried out from the combined transvaginal and transrectal access and was fixing domes sacrospinal vagina, colporrhaphia, augmented transrectal «time 11» mucopexy to a height of 5 cm above the dentate line.Results: sonoelastometric study of stiffness of the muscles of the perineum, tonometric study of vaginal pressure gradient of rest and stress are important diagnostic criteria of pelvic floor functional insufficiency and severity of rectocele. Surgery in 2 patients was more physiological as, accompanied by fewer recurrences of development, higher quality of life and recommended that patients with 3 degrees of rectocele.Summary: the severity of functional insufficiency of muscles of the perineum is the basis of choosing the tactics of surgical treatment of prolapse.